Prior thrombectomy does not affect the surgical complication rate of decompressive hemicraniectomy in patients with malignant ischemic stroke - Walter, Johannes; Alhalabi, Obada; Schönenberger, Silvia; Ringleb, Peter A.; Vollherbst, Dominik; Möhlenbruch, Markus Alfred; Unterberg, Andreas; Neumann, Jan-Oliver (Neurocritical care, 2024)
Even though mechanical recanalization techniques have dramatically improved acute stroke care since the pivotal trials of decompressive hemicraniectomy for malignant courses of ischemic stroke, decompressive hemicraniectomy remains a mainstay of malignant stroke treatment. However, it is still unclear whether prior thrombectomy, which in most cases is associated with application of antiplatelets and/or anticoagulants, affects the surgical complication rate of decompressive hemicraniectomy and whether conclusions derived from prior trials of decompressive hemicraniectomy are still valid in times of modern stroke care.